Lebanon Economic Monitor, Spring 2015 : The Economy of New Drivers and Old Drags - World Bank (Washington, DC, 2015)
The Lebanon Economic Monitor provides an update on key economic developments and policies over the past six months. It also presents findings from recent World Bank work on Lebanon. It places them in a longer-term and global context, and assesses the implications of these developments and other changes in policy on the outlook for Lebanon. Lebanon continues to be impacted by the domestic political stalemate and regional turmoil, particularly along its border with Syria. Economic activity picked up in the second half of 2014. Stronger economic performance and lower oil prices pushed real GDP growth to an estimated 2.0 percent in 2014, compared to 0.9 percent in 2013. One-off cosmetic and unsustainable measures rather than policy actions helped improve the fiscal balance in 2014. We estimate the overall fiscal deficit to have declined by 2.3 percentage points. Declining imports lead an improvement in the current account balance. In 2014, a fall in merchandize imports induced a 4.4 pp reduction in the current account deficit to a still-elevated 22.2 percent of GDP. This trend is projected to continue in 2015 helped by falling oil prices and a depreciating euro, Headline inflation plummeted from 2.7 percent in 2013 to 1.9 percent in 2014 and is expected to remain tempered over the medium term. Lebanon s economy continues to be exposed to external shocks. The border with Syria is increasingly menacing as coordinated attacks by ISIS and Al Nusra are being launched more frequently from their bases in Syria. Inefficiencies in power generation impose sizable macroeconomic costs on Lebanon. The Lebanese electricity sector has been underperforming for decades with considerable socio-economic costs. The macroeconomic impact has been massive.